Pedagogue action and gender and identity issues in children education - Solange Aparecida de Souza Monteiro; Paulo Rennes Marçal Ribeiro (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
The main reflections presented in the article relate to gender and identity issues in children's education in the school education perspective and the experience of the pedagogical professional in the way their subjectivity is produced. In this sense, the development of gender roles and the construction of identity are socially elaborated and learned from birth, based on social and cultural relations established from the first months of life, but it is at the beginning of education that the child begins to perceive the difference between the feminine and the masculine. Consequently, the article prioritizes a number of thematic issues, a process that is therefore plural, polemical and complex, in which daily educational and pedagogical practices incite theoretical questions and problems, at the same time, that new theories and social movements provoke or transform these pedagogical practices. The article brings a study of this subject and is constituted from different disciplinary positions, theoretical and some concepts of the question of gender and identity. It is important to emphasize that understanding these concepts makes it possible to identify the values attributed to men and women as well as the rules of behavior resulting from these values. With this, it is evident: the influence of these values and rules on the functioning of social institutions, such as school; the influence of a possibility that allows us to think about differences without turning them into inequalities, that is, without differences being starting points for discrimination.